On Prospects of Expansion of the Eurasian Economic Union - Yury Vasilyevich Kosov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to the analysis of the possible cooperation between the Eurasian economic union (EAEU) and different countries of the world as China, Egypt, India, Iraq, Japan, New Zealand, Syria, Turkey and others. The authors analyze the possibilities of cooperation of the EAEU with these countries, examine probable profit from the partnership and make a conclusion that the most acceptable form of interaction for today is a free trade zone. Also the authors withdraw, that the participant countries of the Eurasian economic union should pay extra attention to the questions of expanding the EAEU and ensure geopolitical and economic interests of the union.